Periodontal Disease and Diabetes: Knowledge and Attitudes Assessment Project - Rebecca M. Smith; Lora E. Fleming; Kristopher L. Arheart; James D. Wilkinson (University of North Florida, 2007)
There is a growing body of evidence showing that periodontal disease is more prevalent among diabetic patients than among non-diabetic patients. This same evidence also shows that the more poorly controlled the diabetes, the more severe the periodontal disease. However, it is unclear if the increased risk of periodontal disease is known by the diabetes community. Two hundred diabetic patients voluntarily participated in an intervention to increase the diabetic patient's knowledge of and attitudes toward periodontal disease. The study was conducted at the University of Miami-Jackson Memorial Hospital's Diabetes Research Institute (DRI) during the month of May 2005. The purpose of the intervention was to develop an educational brochure designed to increase the diabetic patient's knowledge of and attitude about periodontal disease. The effectiveness of this pamphlet was assessed by administering an anonymous pre-test, immediately followed by the reading of an educational brochure, and then immediate administration of a post-test consisting of the same questions as the pre-test. The data were then analyzed for any changes in knowledge and attitude concerning diabetes and periodontal disease. The results showed that the intervention caused a 33% increase in knowledge (P<0.001); furthermore, although the change in knowledge for subjects with type 1 diabetes was only marginally significant (P=0.066), the change for subjects with type 2 diabetes was very highly significant (P<0.001). Most of the subjects (56%) indicated that they had never been told by their endocrinologist to go see the dentist for a check-up. Therefore, diabetes doctors need to work more closely with their patients and oral health providers to ensure their patients' periodontal health.